Network telemetry technology and its application in automatic network operation and maintenance - Dongfeng MAO; Man JIA; Xiaoming HE; Zhihua LIU (Dianxin kexue)
As a new data acquisition technology, network telemetry has greatly enriched the diversity of data acquisition and expanded the range of traditional OAM data acquisition, whose goal is to realize real-time global network state visibility and traffic visibility.By combining with big data and AI technology, it can reduce human intervention and improve the operation and maintenance level of network automation.Firstly, the problems and challenges faced by the current IP network operation and maintenance were analyzed, and then it was elaborated that the network telemetry technology was the key enabler to realize the automatous network operation and maintenance.On this basis, the application of network telemetry technology in the IP network automatic operation and maintenance was investigated and discussed, and the reference and guidance for the automatic operation and maintenance of large-scale IP network were provided.